1999
DOI: 10.1016/s0094-5765(99)00048-x
|View full text |Cite
|
Sign up to set email alerts
|

Radioisotope electric propulsion of sciencecraft to the outer solar system and near-interstellar space

Abstract: Recent results are presented in the study of radioisotope electric propulsion as a near-term technology for sending small robotic sciencecraft to the outer Solar System and near-interstellar space. Radioisotope electric propulsion (REP) systems are low-thrust, ion propulsion units based on radioisotope electric generators and ion thrusters. Powerplant specific masses are expected to be in the range of 100 to 200 kg/kW of thrust power. Planetary rendezvous missions to Pluto, fast missions to the heliopause (100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…The earliest studies of REP were conducted by Robert Noble of Fermi National Accelerator Laboratory [2][3][4]. He evaluated the technology for sending small robotic spacecraft to the outer Solar System and near-interstellar space.…”
Section: Prior Mission Evaluationsmentioning
confidence: 99%
“…The earliest studies of REP were conducted by Robert Noble of Fermi National Accelerator Laboratory [2][3][4]. He evaluated the technology for sending small robotic spacecraft to the outer Solar System and near-interstellar space.…”
Section: Prior Mission Evaluationsmentioning
confidence: 99%
“…In this work, we detail the mission design studies for such a mission, dubbed the Innovative Interstellar Explorer (IIE) using radioisotope electric propulsion (REP) 20 . In an REP spacecraft, the power system mass is the major mass driver, and overall miniaturization, where possible, is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] More recent work has shown that such radioisotope electric propulsion (REP) spacecraft can orbit or co-orbit various large and small science targets beyond Mars with transit times comparable to large fission-based nuclear electric propulsion (NEP) vehicles, but deliver less science payload with proportionately less power available for science instruments. Although REP vehicles would be much smaller and have less on-board power available for science instruments than fissionbased NEP, REP vehicles, like those using NEP, could conduct missions that are not accessible to chemical, solar electric or aerocapture vehicles.…”
Section: Introductionmentioning
confidence: 99%